2017
DOI: 10.18203/2320-6012.ijrms20173158
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between abscess size and liver function tests in cases of liver abscess

Abstract: Background: Liver abscess has shown a major change in demographics, etiology, diagnosis, and treatment over the past 100 years. The modern diagnostics like ultrasound and computed tomography to locate and drain the abscess have reduced the mortality to 2-12%. However, due to the complications of liver abscess especially the amebic ones the morbidity is still high. This study aims to study the correlation of various LFT parameters with abscess volume for early detection of high risk patients and early treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…The increase in serum ALP levels is observed during cholestasis with increased bile acid concentration, due either to liver parenchymal damage or to biliary obstruction Abnormally high ALP level is considered the most reliable and consistent biochemical indicator of PLA. Although in our study, the ALP level had no relationship with the abscess size, previous studies reported that the ALP level was correlated with the abscess volume and disease duration [20,21]. According to a commonly held view, the reason for the prominent elevation in the level of ALP in the MDRO group was assumed to be the fact that the major cause of MDRO-induced PLAs was biliary disease.…”
Section: Discussioncontrasting
confidence: 74%
“…The increase in serum ALP levels is observed during cholestasis with increased bile acid concentration, due either to liver parenchymal damage or to biliary obstruction Abnormally high ALP level is considered the most reliable and consistent biochemical indicator of PLA. Although in our study, the ALP level had no relationship with the abscess size, previous studies reported that the ALP level was correlated with the abscess volume and disease duration [20,21]. According to a commonly held view, the reason for the prominent elevation in the level of ALP in the MDRO group was assumed to be the fact that the major cause of MDRO-induced PLAs was biliary disease.…”
Section: Discussioncontrasting
confidence: 74%
“…Further analysis based on articles reporting outbreaks indicated that the prevalence could be as high as 68.87% in some outbreaks, such as Puerto Rico. A previous study comparing the prevalence of joint signs/symptoms between dengue and chikungunya infections indicated a lower prevalence (44%) in the former than the latter (90%) virus [32]. Taken together, these findings indicate that joint symptom prevalence associated with ZIKV infection is higher than observed for dengue but lower than for chikungunya.…”
Section: Discussionmentioning
confidence: 46%
“…Jain V et al, in his study on correlation between abscess size and liver function test in cases of liver abscess in the year 2017, stated that abnormally high alkaline phosphatase levels were seen in 94% of cases and hyperbilirubinemia was seen in about 34% of cases. 11 In our study population we noted hyperbilirubinemia in 66.7% of patients, increase in total leukocyte count in 93.3% and raised serum ALP levels in 63.3%.…”
Section: Discussionmentioning
confidence: 46%